Joining dissimilar metals by additive manufacturing: A review - S. Razzaq; Z.X. Pan; H.J. Li; S.P. Ringer; X.Z. Liao (Journal of Materials Research and Technology, 2024)
The demand for lightweight materials, site-specific properties, and customized features drives the need for joining components made from dissimilar materials. However, dissimilar welding poses challenges such as the formation of large heat affected zones and intermetallic compounds at the interface, leading to easy premature failure and cracking. In recent years, additive manufacturing (AM) of dissimilar metallic materials has gained popularity as a solution to these challenges, as evidenced by numerous review articles discussing various aspects of this field. However, a comprehensive review focusing on microstructural analysis at the joint interface of a wide range of materials combinations produced by AM has been lacking. This review aims to address this gap by providing an in-depth examination of microstructures and mechanical properties at the interface for various metal combinations. Furthermore, it delves into different processing approaches and the challenges associated with manufacturing dissimilar structures. This review serves as a valuable resource for beginners in the field, offering a thorough discussion and comparison of the reported results. The paper presents major conclusions and identifies outstanding issues for future investigations. By providing valuable insights crucial for the widespread implementation of dissimilar AM technologies, this analysis will assist current AM processing for dissimilar structures. It is particularly significant for understanding the microstructure at the joint interface of various miscible and immiscible dissimilar structures manufactured using different additive manufacturing techniques.